DIFFERENT INTEGRATED TARGETED YIELD NUTRIENT PRESCRIPTION MANAGEMENT OF RICE-BLACKGRAM SEQUENCE - D. MOUNIKA; M. MARTIN LUTHER; K. CHANDRA SEKHAR; G. KISHORE BABU (The Bioscan, 2019)
A field experiment was conducted at the Agricultural College farm, Bapatla, during kharif and rabi 2017-18 and 2018-19. The experiment was conducted with variety BPT-5204 in a Randomized Block Design with ten treatments and three replications. The Seed yield, Grain yield of rice- blackgram crops, system productivity of rice-blackgram sequence and economics of rice-blackgram were recorded with soil test based fertilizer recommendation with 10 t ha-1 FYM application which was at par with soil test based fertilizer recommendation alone and 7.5 tha-1 targeted yield recommendation along with FYM (T5 and T10) and RDF with FYM (T6). Seed yield of blackgram was significantly higher with soil test based fertilizer recommendation with 10 t ha-1 FYM application which was statistically at par with soil test based fertilizer recommendation alone (T2) and 7.5 t ha- 1 targeted yield fertilizer recommendation with FYM (T10) compared to the rest of the treatments.